Alanine aminotransferase to aspartate aminotransferase ratio and hepatitis B virus on metabolic syndrome: a community-based study - Lin, Ming-Shyan; Lin, Huang-Shen; Chang, Ming-Ling; Tsai, Ming-Horng; Hsieh, Yung-Yu; Lin, Yu-Sheng; Tsai, Meng-Shu; Yang, Chia-Ling; Chen, Mei-Yen (Frontiers in Endocrinology, 2022)
Background: The serum aminotransferases elevation in metabolic syndrome (MetS) reflected hepatosteatosis, but there is a conflict with the co-existence of viral hepatitis, especially for hepatitis B virus (HBV). Thus, this study aimed to investigate the relationship between the alanine aminotransferase (ALT)/aspartate aminotransferase (AST) ratio, MetS, and HBV infection in the rural Taiwanese population. Methods: We conducted a cross-sectional analysis in southern Taiwan between March and December 2019. Multivariable logistic regression analyses adjusted for demographics, education, dietary behaviors, irregular exercise, substance use, and viral markers were performed to investigate the association between the ALT/AST ratio and MetS. Results: Altogether, 2,416 participants (891 men and 1,525 women; mean age, 64.1 ± 14.9 years) were enrolled. Of the participants, 22.7% (n = 519) were seropositive for viral hepatitis. In the multivariable analysis, age (odds ratio (OR) 1.02, 95% CI 1.01–1.03, p < 0.001), ALT/AST ratio >1 (OR 2.63, 95% CI 2.15–3.21, p < 0.001), education (OR 0.96, 95% CI 0.94–0.98, p < 0.001), and HBV seropositivity (OR 0.70, 95% CI 0.52–0.95, p = 0.021) were associated with the risk of MetS. The area under curve of the ALT/AST ratio was 0.62 (95% CI 0.60–0.64, p < 0.001, and the cutoff value was >0.852 for the Youden index. Conclusion: An ALT/AST ratio > 1 could be a simple index for MetS prediction during community check-ups. In contrast to age and betel nut chewing, HBV seropositivity and higher education might be inversely associated with MetS. Aggressive health promotion for MetS prevention has emerged as essential in participants without HBV and with lower education levels. Further large-scale, longitudinal studies are needed to unlink these correlations.